Effective project management - Roberts, Paul , 1964- (Business success, 2011)
Whether organising an important event or heading up a large team, running a project can be a daunting process. This title covers various aspects of how to manage a project, including how to manage changing targets, how to plan quality, timescales and budgets, how to identify and manage risks and how to deliver your project